KAJIAN HUKUM TENTANG HUBUNGAN EKSEKUTIF DAN LEGISLATIF DALAM PENYUSUNAN DAN PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) YANG DEMOKRATIS - Rauf, Iswan (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
Form of Equalization of Perceptions between the Executive and Legislature in the preparation of democratic Regional Expenditure Revenue budgets. The research method used is normative research, namely, legal research carried out utilizing a literature review and review of legislation. The results showed that the partnership relationship means that the Regional Government and the Regional People's Representative Council are both partners in making regional policies to implement regional autonomy according to their respective functions by taking into account applicable regulations and Equalizing Perceptions Between the Executive and the Legislature in the Preparation of Democratic Regional Budgets In the preparation of the Regional Budget that the parties involved must have high commitment to set the regional budget promptly and implement the budget that has been set effectively and efficiently. Communication between the executive and legislature must be based on transparency and accountability.